Does Macroeconomic Fluctuation Matter for The Composite Stock Price Index? - Adin Juli Wibowo; Rifki Khoirudin (Department of Development Economics, Universitas Sriwijaya, 2022)
This study aims to investigate the effect of interest rates, inflation, rupiah exchange rate, money supply, and exports on the composite stock price index (CSPI) in Indonesia. The data used is secondary data obtained from the Indonesian Statistics Agency (BPS) and Central Bank of Indonesia for the period from January 2014 to May 2021. This study applies a multiple linear regression model. The findings of this study indicate that interest rates, money supply, and exports have a positive sign and have a significant effect on the composite stock price index, meanwhile the rupiah exchange rate has a negative sign and a significant effect on CSPI. However, inflation has no significant effect on the composite stock price index.The implication of the results of this study is that macroeconomic variables are very important in highlighting transactions in the capital market, especially on fluctuations in the composite stock price index, these findings provide results that still need to be observed by policy makers. On the one hand, interest rates and inflation must remain under control. In addition, exports must also be increased to increase transactions in the capital market, foreign exchange and maintain the rupiah exchange rate for Indonesia